CHEMICAL CHARACTERISTICS OF DISSOLVED ORGANIC NITROGEN IN AN OLIGOTROPHIC SUBTROPICAL COASTAL ECOSYSTEM - Maie N.; Parish K.J.; Watanabe A.; Knicker H.; Benner R.; Abe T.; Kaiser K.; Jaffe R. (My University, 2006)
Water samples were collected from rivers and estuarine environments within the Florida Coastal Everglades (FCE) ecosystem, USA, and ultrafiltered dissolved organic matter (UDOM; <0.7 ?m, >1 kDa) was isolated for characterization of its source, bioavailability and diagenetic state. A combination of techniques, including 15N cross-polarization magic angle spinning nuclear magnetic resonance (15N CPMAS NMR) and X-ray photoelectron spectroscopy (XPS), were used to analyze the N components of UDOM. The concentrations and compositions of total hydrolysable amino acids (HAAs) were analyzed to estimate UDOM bioavailability and diagenetic state. Optical properties (UV-visible and fluorescence) and the stable isotope ratios of C and N were measured to assess the source and dynamics of UDOM. Spectroscopic analyses consistently showed that the major N species of UDOM are in amide form, but significant contributions of aromatic-N were also observed. XPS showed a very high pyridinic-N concentration in the FCE-UDOM (21.7 ? 2.7%) compared with those in other environments. The sources of this aromatic-N are unclear, but could include soot and charred materials from wild fires. Relatively high total HAA concentrations (4 ? 2% UDOC or 27 ? 4% UDON) are indicative of bioavailable components, and HAA compositions suggest FCE-UDOM has not undergone extensive diagenetic processing. These observations can be attributed to the low microbial activity and a continuous supply of fresh UDOM in this oligotrophic ecosystem. Marsh plants appear to be the dominant source of UDOM in freshwater regions of the FCE, whereas seagrasses and algae are the dominant sources of UDOM in Florida Bay. This study demonstrates the utility of a multi-technique and multi-proxy approach to advance our understanding of DON biogeochemistry. ? 2006 Elsevier Inc. All rights reserved.
Keywords: COASTAL WATER; DISSOLVED ORGANIC NITROGEN; OLIGOTROPHIC ENVIRONMENT; OPTICAL PROPERTY; SUBTROPICAL REGION; FLORIDA BAY; ALGAE